THE TEACHING OF THE FUNDAMENTALS OF MODALITY HANDBALL THROUGH GAMES AND JINKS POPULAR (Fiep Bulletin - online, 2011)
This pedagogical practice is aimed at presenting a methodological approach for the development of classes Sports Initiation in the sport of Handball, taught by a physical education teacher for students in the classes of 1, 2, 3 and 4 years of High School Integrated Federal Institute of Alagoas - Maceió Campus in the years 2009 and 2010. The practice has happened on two occasions, at first, each student researched and brought in writing or playing a game popular to be applied in its traditional format, and secondly, these activities were modified and adapted, transformed into other forms execution. The central idea of the purpose of this study is to unite the field of general education to vocational education enabling a comprehensive, aiming at the development of an individual, allowing a recovery of body culture in the region where the student is entered, and taking into account the teaching in cultural diversity. With the evaluation of this methodology perspective novelty recreational deployed as a strategy of teaching Handball, we conclude that the games and popular games contribute to the formation of the individual, they offer several ways to solve problems, making decisions and preparing in new ways from a primitive form. Forms, so a generation based on principles of brotherhood, solidarity, cooperation, co-education and physical education as having the axis of that process, from the perspective of educational and social values with the game and play as a means of popular education.
Keywords: Physical Education; Methodology; Handball; Culture; Fun Games and Recreation